Association between walking time spent and high sensitivity C-reactive protein level among obese women - Daud, Azlina; Shahadan, Siti Zuhaidah (Elsevier Doyma, 2019)
Objective This study aims to assess the association between the walking time spent and high sensitivity C-reactive protein (hs-CRP) level to determine the risk for cardiovascular disease (CVD) among obese women. Methods Cross-sectional study was conducted in Kuantan, Pahang. The purposive sampling method was chosen. 76 obese women aged 18 years old and above were included in the study. Data were collected by using the set of the self-reported questionnaire consisted of socio-demographic and the walking time for the past 7 days. The sample blood test was taken to check for hs-CRP level. Results Walking time spent in minutes was found to be significantly inverse associated with the hs-CRP level (p = 0.040) among obese women. Conclusion The increase in walking time spent can help reduce the hs-CRP level, therefore reduce the risk for CVD.